Inclusive Education: Meaning, Need and Suggestions: Promoting Equality and Access in Education (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is a human right which ought to be accessible to everyone. Every citizen of a country has the right to improve their lives through education. The concept of inclusive education emerges from the human rights to education pronounced in universal declaration of Human rights in 1949. Rights of children as mentioned in Article 2 of the convention are equally important. It says that segregation of children with challenging needs is morally unjustifiable a violation of human rights. In other words, we can say that all children have the right to receive the type of education that does not discriminate on the grounds of disability, religion, language, gender, capabilities and so on.